Emulsion
By using a combination of block copolymers and dispersants in the emulsion, the problem that existing biodegradable resins are difficult to meet higher biodegradability needs after increasing environmental awareness, and better biodegradability and dispersion stability are achieved.
Patent Information
- Application Number
- CN202380057646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-28
AI Technical Summary
The particles and dispersions of existing biodegradable resins are difficult to meet higher biodegradable needs after increasing environmental awareness.
An emulsion is used to combine a block copolymer (I) and a dispersant (II). The block copolymer (I) contains polylactic acid units (A) and polyester units (B), the polyester unit (B) consists of aliphatic diol and aliphatic dicarboxylic acids, and the dispersant (II) is a vinyl alcohol-based polymer.
An emulsion with better biodegradability is achieved, and the dispersion stability and biodegradability of the emulsion are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an emulsion having excellent biodegradability. Background Art
[0002] From the perspective of environmental protection, biodegradable resins are being actively developed. Biodegradable resins are plastics that are formed from biomass by the participation of natural microorganisms and other organisms, and are ultimately decomposed into water and carbon dioxide and returned to nature, which can also reduce the generation of carbon dioxide.
[0003] In order to apply biodegradable resins to a wide range of fields such as coatings, adhesives, printing, fibers, and films, technologies for micronizing biodegradable resins and development of dispersions containing micronized biodegradable resins are actively being pursued.
[0004] As such a technology, for example, Patent Documents 1 to 3 are proposed. Patent Document 1 discloses biodegradable polyester resin microparticles such as polylactic acid resin and a method for producing the same. Patent Document 2 discloses an aqueous dispersion of a hydrolytically unstable polymer that does not substantially contain volatile organic compounds, wherein the hydrolytically unstable polymer contains a biodegradable polymer. Patent Document 3 discloses an aqueous dispersion of a biodegradable resin, which is an aqueous dispersion in which a biodegradable resin is dispersed in water and contains a specific polyvinyl alcohol as a dispersant.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-2302
[0008] Patent Document 2: Japanese Patent Application No. 2019-507229
[0009] Patent Document 3: Japanese Patent Application Publication No. 2004-99883 Summary of the invention
[0010] Problems to be solved by the invention
[0011] It is presumed that the biodegradable resin microparticles and the dispersions containing the biodegradable resin described in Patent Documents 1 to 3 have a certain degree of biodegradability. However, due to the increase in environmental awareness, there is a demand for better biodegradability.
[0012] Therefore, an object of the present invention is to provide an emulsion having excellent biodegradability.
[0013] Means for solving problems
[0014] As a result of intensive studies to solve the above-mentioned problems, the present inventors have come up with the following invention and found that the problems can be solved.
[0015] That is, the present invention is as follows.
[0016] [1] An emulsion comprising a block copolymer (I) and a dispersant (II),
[0017] The block copolymer (I) comprises a block structural unit (A) comprising a polylactic acid unit (a) as a main component and a block structural unit (B) comprising a polyester unit (b) as a main component.
[0018] [2] The emulsion according to [1], wherein the block copolymer (I) accounts for 50% by mass or more and 99% by mass or less relative to 100% by mass of the total of the block copolymer (I) and the dispersant (II).
[0019] [3] The emulsion according to [1] or [2], wherein the polyester unit (b) comprises units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2),
[0020] The aliphatic diol (b1) is a diol having an alkyl group as a branch chain.
[0021] [4] The emulsion according to [3] above, wherein the aliphatic diol (b1) has 10 or less carbon atoms.
[0022] [5] The emulsion according to [3] or [4], wherein the aliphatic diol (b1) has 5 or more carbon atoms.
[0023] [6] The emulsion according to any one of [3] to [5], wherein the branched chain of the aliphatic diol (b1) is a methyl group.
[0024] [7] The emulsion according to any one of [1] to [6], wherein the block structural unit (A) accounts for 5% by mass or more and 95% by mass or less relative to 100% by mass of the total of the block structural unit (A) and the block structural unit (B).
[0025] [8] The emulsion according to any one of [1] to [7], wherein the dispersant (II) is a vinyl alcohol polymer.
[0026] [9] The emulsion according to any one of [1] to [8] above, wherein the particle size is 100 to 1,000 nm.
[0027]
[10] A method for producing an emulsion, which is the method for producing an emulsion according to any one of [1] to [9] above, comprising:
[0028] A step of dispersing the block copolymer (I) dissolved in an organic solvent in an aqueous medium in the presence of the dispersant (II).
[0029]
[11] The method for producing an emulsion according to
[10] , further comprising the step of removing the organic solvent.
[0030] Effects of the Invention
[0031] According to the present invention, an emulsion having excellent biodegradability can be provided. DETAILED DESCRIPTION
[0032] Hereinafter, an example of an embodiment of the present invention will be described. However, the embodiment described below is an example for embodying the technical idea of the present invention, and the present invention is not limited to the following description.
[0033] In this specification, preferred embodiments are shown, but a combination of two or more preferred embodiments is also a preferred embodiment. Regarding matters shown in numerical ranges, when there are several numerical ranges, their lower limits and upper limits can be selectively combined to form a preferred embodiment. In addition, when a numerical range of "XX to YY" is recorded, it means "above XX and below YY".
[0034] In this specification, "-" unit (here, "-" means a polymer) means "a structural unit derived from -". For example, "polylactic acid unit" means "a structural unit derived from polylactic acid", and "polyester unit" means "a structural unit derived from polyester".
[0035] In this specification, unless otherwise specified, the "main chain" of a polymer refers to the longest molecular chain in the polymer molecule.
[0036] In the present invention, "solid" means having no fluidity at room temperature (23°C) and in an unpressurized state.
[0037] [Lotion]
[0038] The emulsion of this embodiment contains a block copolymer (I) and a dispersant (II). The block copolymer (I) contains a block structural unit (A) and a block structural unit (B), wherein the block structural unit (A) contains a polylactic acid unit (a) as a main component and the block structural unit (B) contains a polyester unit (b) as a main component.
[0039] The present inventors have conducted various studies on formulations for imparting excellent biodegradability to an emulsion. As a result, the present inventors have found that an emulsion containing a block copolymer (I) comprising a block structural unit (A) and a block structural unit (B), and a dispersant (II) is an effective formulation for achieving excellent biodegradability.
[0040] <Block copolymer (I)>
[0041] The block copolymer (I) comprises a block structural unit (A) and a block structural unit (B), wherein the block structural unit (A) comprises a polylactic acid unit (a) as a main component, and the block structural unit (B) comprises a polyester unit (b) as a main component. By comprising the polylactic acid unit (a), it is easy to adjust the melting point to above room temperature, and the handling property of the block copolymer (I) is improved. In addition, by comprising the block structural unit (B) containing the polyester unit (b) as a main component, the biodegradability and hydrolysis resistance of the block copolymer (I) are improved.
[0042] 《Block structural unit (A)》
[0043] 〈Polylactic acid unit (a)〉
[0044] The block structural unit (A) contains the polylactic acid unit (a) as a main component.
[0045] The above-mentioned “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (A).
[0046] The content of the polylactic acid unit (a) in the block structural unit (A) is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the polylactic acid unit (a) contained in the block structural unit (A) is not limited, for example, it is 100% by mass or less.
[0047] The polylactic acid constituting the polylactic acid unit (a) may be prepared by a direct condensation method of lactic acid or by a ring-opening polymerization method of lactide. As the lactic acid, for example, at least one selected from L-lactic acid, D-lactic acid and DL-lactic acid may be used. As the lactide, for example, at least one selected from L-lactide, D-lactide, DL-lactide and meso-lactide may be used.
[0048] In addition, the polylactic acid may be poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid, or a stereocomplex polylactic acid obtained by mixing poly-L-lactic acid and poly-D-lactic acid. From the viewpoint of cost, availability of raw materials, and handleability of the block copolymer (I), the polylactic acid is preferably poly-L-lactic acid, poly-D-lactic acid, and poly-DL-lactic acid, and more preferably poly-L-lactic acid and poly-D-lactic acid.
[0049] On the other hand, from the viewpoint of the cost and complexity of synthesis, the polylactic acid is preferably not a stereocomplex polylactic acid.
[0050] From the viewpoint of exhibiting more excellent biodegradability, the block structural unit (A) preferably contains 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid. For example, it is an example of a preferred embodiment that the block structural unit (A) is composed of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid, that is, structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid account for 100% by mass.
[0051] <Units (a') other than the polylactic acid unit (a)>
[0052] The block structural unit (A) may or may not contain a unit (a′) other than the polylactic acid unit (a).
[0053] The monomer constituting the unit (a′) is not particularly limited as long as the effects of the present invention are not impaired.
[0054] The content of the unit (a′) in the block structural unit (A) is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, and further preferably 10% by mass or less.
[0055] <Number average molecular weight of block structural unit (A)>
[0056] The number average molecular weight of the block structural unit (A) is preferably 1,000 to 100,000, more preferably 5,000 to 25,000, further preferably 8,200 to 15,000, particularly preferably 5,200 to 15,000. Within the above numerical range, productivity is excellent and the viscosity tends to be within a range that allows easy handling of the emulsion.
[0057] In addition, when the block copolymer (I) has a plurality of block structural units (A), the number average molecular weight of the block structural unit (A) refers to the total of all blocks.
[0058] The number average molecular weight of the block structural unit (A) can be determined from the number average molecular weight of the block copolymer (I) described below and the mass content of the block structural unit (A).
[0059] 《Block structural unit (B)》
[0060] The block structural unit (B) contains the polyester unit (b) as a main component.
[0061] The above-mentioned “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (B).
[0062] The content of the polyester unit (b) in the block structural unit (B) is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the polyester unit (b) contained in the block structural unit (B) is not limited, and is, for example, 100% by mass or less.
[0063] From the viewpoint of exhibiting more excellent biodegradability, the polyester unit (b) preferably contains a unit derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). Specifically, the polyester unit (b) preferably contains a unit derived from a polyester obtained by reacting an aliphatic diol (b1) with an aliphatic dicarboxylic acid (b2). The polyester unit (b) may or may not contain a unit derived from a monomer other than the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2).
[0064] The monomers other than the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) are not particularly limited as long as the effects of the present invention are not impaired.
[0065] The total amount of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) in the polyester unit (b) is preferably 90 mol % or more, more preferably 95 mol % or more, further preferably 99 mol % or more, and may be 100 mol %.
[0066] <Aliphatic diol (b1)>
[0067] The number of carbon atoms of the aliphatic diol (b1) is preferably 5 or more, more preferably 6 or more, from the viewpoint of exhibiting excellent hydrolysis resistance, and is preferably 10 or less, more preferably 9 or less, further preferably 8 or less, particularly preferably 7 or less, from the viewpoint of exhibiting even better biodegradability.
[0068] From the viewpoint of suppressing crystallization of the block structural unit (B) and exerting further excellent biodegradability, and from the viewpoint of improving the hydrolysis resistance of the block structural unit (B) as an emulsion, the aliphatic diol (b1) preferably has an alkyl group as a side chain. That is, it is preferred that the polyester unit (b) contains a unit derived from the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2), and the aliphatic diol (b1) has an alkyl group as a side chain.
[0069] Here, the “branched chain” in the aliphatic diol (b1) refers to a partial structure branched from the “main chain” in the aliphatic diol (b1), and no hydroxyl group is bonded to the terminal.
[0070] Furthermore, the "main chain" in the aliphatic diol (b1) is a partial structure of a molecular chain consisting of a plurality of atoms, preferably carbon atoms, connecting the two hydroxyl groups in the molecule at both ends. Therefore, the two hydroxyl groups in the aliphatic diol (b1) are located at both ends of the "main chain" in the aliphatic diol (b1).
[0071] It is speculated that if the aliphatic diol (b1) has a side chain as an alkyl group, the block structure unit (B) is likely to become an amorphous polymer, so that during biodegradation, microorganisms are more likely to enter the polymer structure, and the biodegradability is more excellent. However, the block structure unit (B) being an amorphous polymer is only one factor that affects biodegradability. This is because it can be considered that biodegradation is carried out by various factors such as whether the composite microorganism recognizes the amorphous structure as food, whether the enzyme or microorganism is easy to access, the steric hindrance of the main chain, the melting point, and the crystallinity. Therefore, the effect of the present invention is not obtained as long as it is an amorphous polymer.
[0072] When the aliphatic diol (b1) has an alkyl group as a branch chain, the “number of carbon atoms” of the aliphatic diol (b1) refers to the number of carbon atoms of the aliphatic diol (b1) as a whole including the number of carbon atoms forming the alkyl group.
[0073] In the aliphatic diol (b1), the number of branches is preferably 1 or 2, and more preferably 1. In addition, the branch is preferably a methyl group, an ethyl group, and a propyl group, more preferably a methyl group and an ethyl group, and further preferably a methyl group. In addition, when the aliphatic diol (b1) has a plurality of branches, each branch may be the same or different.
[0074] From the viewpoint of being easy to react with dicarboxylic acid and being able to easily produce a triblock copolymer, the aliphatic diol (b1) preferably has a side chain at or above the γ position away from the hydroxyl group and a methyl group with little steric hindrance. Furthermore, from the viewpoint of having even better biodegradability, the aliphatic diol (b1) preferably has hydroxyl groups at both ends of the main chain.
[0075] Examples of the aliphatic diol (b1) having 5 to 10 carbon atoms and having an alkyl group as a branch chain include 2,2-dimethyl-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-methyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-methyl-1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-2 ,4-pentanediol, 1,4-pentanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,5-pentanediol, 2,4-dimethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 2-ethyl-1,6-hexanediol, 2-methyl-1,8-octanediol, 2,7-dimethyl-1,8-octanediol, 2-methyl-1,9-nonanediol, etc. The aliphatic diol (b1) is preferably 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol and 2,4-diethyl-1,5-pentanediol, and more preferably 3-methyl-1,5-pentanediol.
[0076] The aliphatic diol (b1) may be used alone or in combination of two or more.
[0077] <Aliphatic dicarboxylic acid (b2)>
[0078] From the viewpoint of exhibiting excellent hydrolysis resistance, the number of carbon atoms of the aliphatic dicarboxylic acid (b2) is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more, and from the viewpoint of exhibiting even more excellent biodegradability, it is preferably 12 or less, more preferably 10 or less, and even more preferably 8 or less.
[0079] Examples of the aliphatic dicarboxylic acid (b2) having a carbon number of 4 or more and 12 or less include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and decanedicarboxylic acid. The aliphatic dicarboxylic acid (b2) is preferably succinic acid, adipic acid, and sebacic acid, more preferably adipic acid and sebacic acid, and still more preferably adipic acid.
[0080] The aliphatic dicarboxylic acid (b2) may be used alone or in combination of two or more.
[0081] <Preferred combination of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2)>
[0082] From the viewpoint of exhibiting further excellent biodegradability, a combination of 3-methyl-1,5-pentanediol and adipic acid, a combination of 2-methyl-1,3-propanediol and succinic acid, and a combination of 2,4-diethyl-1,5-pentanediol and adipic acid are examples of preferred embodiments, and a combination of 3-methyl-1,5-pentanediol and adipic acid is an example of a more preferred embodiment.
[0083] <Ratio of aliphatic diol (b1) to aliphatic dicarboxylic acid (b2)>
[0084] The charging molar ratio [aliphatic diol (b1) / aliphatic dicarboxylic acid (b2)] when reacting the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) is preferably 1.4 / 1 to 1 / 1.4, more preferably 1.2 / 1 to 1 / 1.2, and further preferably 1.15 / 1 to 1 / 1.15.
[0085] <Unit (b') other than polyester unit (b)>
[0086] The block structural unit (B) may contain a unit (b') other than the polyester unit (b).
[0087] The monomer constituting the unit (b′) is not particularly limited as long as the effects of the present invention are not impaired.
[0088] The content of the unit (b′) in the block structural unit (B) is preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, further preferably 15% by mass or less, particularly preferably 10% by mass or less.
[0089] <Number average molecular weight of block structural unit (B)>
[0090] The number average molecular weight of the block structural unit (B) is preferably 2,500 or more, more preferably 4,000 or more, and even more preferably 5,000 or more. In addition, the number average molecular weight of the block structural unit (B) is preferably less than 100,000, more preferably less than 50,000, even more preferably less than 30,000, even more preferably less than 20,000, particularly preferably less than 15,000, and most preferably less than 10,000.
[0091] When the content is within the above numerical range, the block copolymer (I) tends to be excellent in productivity.
[0092] The number average molecular weight of the block structural unit (B) can be determined by gel permeation chromatography (GPC), and specifically, can be measured by the method described in Examples.
[0093] Structural unit ratio
[0094] The block structural unit (A) accounts for preferably 5 mass % or more, more preferably 15 mass % or more, further preferably 25 mass % or more, particularly preferably 35 mass % or more, based on 100 mass % of the total of the block structural unit (A) and the block structural unit (B).
[0095] The block structural unit (A) accounts for preferably 95% by mass or less, more preferably 85% by mass or less, further preferably 75% by mass or less, and particularly preferably 60% by mass or less, based on 100% by mass of the total of the block structural unit (A) and the block structural unit (B).
[0096] When the proportion of the block structural unit (A) is 5% by mass or more, the block copolymer (I) tends to have further improved handling properties. When the proportion of the block structural unit (A) is 95% by mass or less, the block copolymer (I) tends to have improved flexibility, biodegradability, and the like.
[0097] From the viewpoint of handling, the proportion of the block structural unit (A) is more preferably 10% by mass or more, and further preferably 15% by mass or more. In addition, from the viewpoints of flexibility, biodegradability, etc., the proportion of the block structural unit (A) is more preferably 80% by mass or less, further preferably 75% by mass or less, further preferably 70% by mass or less, and particularly preferably 60% by mass or less.
[0098] The proportion of the block structural units (A) can be determined by 1 H-NMR can be determined, specifically, by the method described in Examples.
[0099] The total content of the block structural unit (A) and the block structural unit (B) in the block copolymer (I) is preferably 90% by mass or more, more preferably 95% by mass or more, and may be 100% by mass. The upper limit of the total content of the block structural unit (A) and the block structural unit (B) in the block copolymer (I) is not limited, and is, for example, 100% by mass or less.
[0100] The block copolymer (I) may or may not contain units other than the block structural unit (A) and the block structural unit (B).
[0101] The units other than the block structural unit (A) and the block structural unit (B) are not particularly limited as long as the effects of the present invention are not impaired.
[0102] The content of units other than the block structural unit (A) and the block structural unit (B) in the block copolymer (I) is preferably 10% by mass or less, more preferably 5% by mass or less.
[0103] 《Number average molecular weight of block copolymer (I)》
[0104] From the viewpoint of handling properties and hydrolysis resistance, the number average molecular weight of the block copolymer (I) is preferably 5,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more. From the viewpoint of productivity, the number average molecular weight of the block copolymer (I) is preferably less than 200,000, more preferably less than 100,000, even more preferably less than 60,000, even more preferably 50,000 or less, particularly preferably 40,000 or less, and most preferably 20,000 or less.
[0105] The number average molecular weight of the block copolymer (I) can be determined by gel permeation chromatography (GPC), and specifically, can be measured by the method described in Examples.
[0106] 《Bonding form of block copolymer (I)》
[0107] The bonding form of the block copolymer (I) is preferably a triblock type and a diblock type, and more preferably a triblock type. The block copolymer (I) may also be a mixture of a triblock type and a diblock type. Specifically, the bonding form is preferably [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)].
[0108] <Dispersant (II)>
[0109] The dispersant (II) is not particularly limited as long as it can produce an emulsion containing the block copolymer (I) within a range not impairing the effects of the present invention.
[0110] As the dispersant (II), for example, a water-soluble polymer, a surfactant, etc. can be used.
[0111] Examples of the water-soluble polymer include vinyl alcohol polymers such as polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, sodium polyacrylate, sodium polymethacrylate, and the like.
[0112] Examples of the surfactant include nonionic surfactants such as sorbitan monolaurate, polyoxyethylene sorbitan monolaurate, polyoxyethylene coconut fatty acid glyceride, polyoxyethylene castor oil, polyglycerol oleate, polyoxyethylene laurylamine, and polyoxyethylene sorbitan tetraoleate; anionic surfactants such as alkylbenzene sulfonates such as sodium dodecylbenzene sulfonate, alkyl sulfates such as sodium dodecyl sulfate and sodium lauryl sulfate, sodium N-cocoyl methyl taurate, sodium di-2-ethylhexyl sulfosuccinate, sodium 2-ethylhexyl sulfate, and sodium salt of α-sulfo fatty acid methyl ester; cationic surfactants such as benzalkonium chloride, dodecyltrimethylammonium chloride, tetradecylamine acetate, didecyldimethylammonium chloride, and tetradecyldimethylbenzyl ammonium chloride; and amphoteric surfactants such as coconut dimethylaminoacetic acid betaine, coconut fatty acid amidopropyl dimethylaminoacetic acid betaine, sodium lauryldiaminoethylglycinate, and monosodium laurylaminodiacetic acid.
[0113] From the viewpoint of improving dispersion stability and exerting further excellent biodegradability, the dispersant (II) is preferably a water-soluble polymer and anionic surfactant, and more preferably a water-soluble polymer.
[0114] From the viewpoint of improving dispersion stability and exerting further excellent biodegradability, the water-soluble polymer is preferably a vinyl alcohol polymer.
[0115] From the viewpoint of improving dispersion stability and exerting further excellent biodegradability, the anionic surfactant is preferably an alkylbenzene sulfonate, and more preferably sodium dodecylbenzene sulfonate.
[0116] When a vinyl alcohol polymer is used as the dispersant (II), the saponification degree of the vinyl alcohol polymer is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit is preferably 100 mol% or less, more preferably 99 mol% or less, more preferably 98 mol% or less, further preferably 95 mol% or less, and particularly preferably 90 mol% or less.
[0117] The saponification degree can be measured, for example, by the saponification degree measuring method described in JIS-K6726 (1994). In addition, from the viewpoint of emulsification ability, the vinyl alcohol polymer is preferably a partially saponified type.
[0118] When a vinyl alcohol polymer is used as the dispersant (II), the viscosity of the vinyl alcohol polymer as a 4 mass % aqueous solution (20° C.) is preferably 3 to 120 mPa·s, more preferably 4 to 70 mPa·s, further preferably 8 to 60 mPa·s, and particularly preferably 20 to 50 mPa·s.
[0119] The viscosity can be measured by the viscosity measuring method described in JIS-K6726 (1994).
[0120] <Dispersion medium>
[0121] The dispersion medium is preferably an aqueous medium with water as the main component. In the aqueous medium with water as the main component, a soluble water-soluble organic solvent (alcohols, ketones, etc.) can be contained in any proportion with water. Here, "aqueous medium with water as the main component" refers to a dispersion medium containing 50% by mass or more of water. From the viewpoint of cost and environmental load, the dispersion medium is preferably an aqueous medium containing 90% by mass or more of water, more preferably water.
[0122] From the viewpoints of productivity, handling properties and dispersion stability, the content of the dispersion medium in the emulsion is preferably 50% by mass or more, more preferably 65% by mass or more, further preferably 75% by mass or more, further preferably 80% by mass or more, and preferably 99% by mass or less, more preferably 97% by mass or less, further preferably 95% by mass or less.
[0123] <Components other than block copolymer (I), dispersant (II) and dispersion medium>
[0124] The emulsion may contain components other than the block copolymer (I), the dispersant (II) and the dispersion medium.
[0125] Examples of components other than the block copolymer (I), the dispersant (II) and the dispersion medium include polymers other than the block copolymer (I), colorants (pigments or dyes), defoamers, antioxidants, ultraviolet absorbers and the like.
[0126] The content of the block copolymer (I), the dispersant (II) and the components other than the dispersion medium in the emulsion is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0127] <Ratio of block copolymer (I) and dispersant (II)>
[0128] With respect to the total of 100 mass % of the block copolymer (I) and the dispersant (II), from the viewpoint of the effective ingredient, the block copolymer (I) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 65 mass % or more, further preferably 70 mass % or more, and particularly preferably 75 mass % or more, and from the viewpoint of improving the dispersion stability and the viscosity range of easy handling, it is 99 mass % or less, more preferably 97 mass % or less, further preferably 96 mass % or less, further preferably 90 mass % or less, and particularly preferably 85 mass % or less. That is, with respect to the total of 100 mass % of the block copolymer (I) and the dispersant (II), the block copolymer (I) is preferably 50 to 99 mass %, more preferably 60 to 97 mass %, further preferably 65 to 96 mass %, further preferably 70 to 90 mass %, and particularly preferably 75 to 85 mass %.
[0129] From the viewpoint of improving dispersion stability and the viscosity range for easy handling, the amount of the dispersant (II) is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 4% by mass or more, further preferably 5% by mass or more, particularly preferably 10% by mass or more, and most preferably 15% by mass or more, relative to 100% by mass of the total of the block copolymer (I) and the dispersant (II). From the viewpoint of improving productivity and the amount of effective ingredients, it is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, further preferably 30% by mass or less, particularly preferably 28% by mass or less, and most preferably 25% by mass or less. That is, relative to 100% by mass of the total of the block copolymer (I) and the dispersant (II), the amount of the dispersant (II) is preferably 1 to 50% by mass, more preferably 3 to 40% by mass, further preferably 4 to 35% by mass, further preferably 5 to 30% by mass, particularly preferably 10 to 28% by mass, and most preferably 15 to 25% by mass.
[0130] From the viewpoint of increasing the amount of effective ingredients, the total content of the block copolymer (I) and the dispersant (II) in the emulsion is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more. From the viewpoint of making the emulsion have a viscosity that is easy to handle, it is preferably 50% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less. That is, the total content of the block copolymer (I) and the dispersant (II) in the emulsion is preferably 1 to 50% by mass, more preferably 3 to 30% by mass, and further preferably 5 to 20% by mass.
[0131] [Solid content in emulsion]
[0132] The solid content in the emulsion is preferably 1 to 50% by mass, more preferably 3 to 30% by mass, and further preferably 5 to 20% by mass. When the solid content in the emulsion is within the above range, more excellent dispersion stability tends to be easily obtained.
[0133] The solid content in the emulsion refers to a value obtained by measuring the residual content after heat drying at 140° C. until there is no change in weight using a heat drying type moisture meter.
[0134] In addition, from the viewpoint of effective ingredients, the total content of the block copolymer (I) and the dispersant (II) in the solid content of the emulsion is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, and may include 100% by mass.
[0135] [Emulsion particle size]
[0136] From the viewpoint of dispersion stability, the particle size of the emulsion is preferably 100 to 1,000 nm, more preferably 130 to 800 nm, further preferably 150 to 600 nm, further preferably 180 to 400 nm, and particularly preferably 200 to 350 nm.
[0137] In addition, in this specification, "particle diameter" means the average particle diameter measured by the dynamic light scattering measuring apparatus mentioned later.
[0138] [Long-term dispersion stability of emulsion]
[0139] Regarding the dispersion stability of the emulsion, from the viewpoint of long-term storage stability, it is desired that the resin does not precipitate at 23° C. for preferably 2 weeks or more, more preferably 1 month or more, and further preferably 3 months or more.
[0140] In addition, in this specification, "long-term dispersion stability" means the value evaluated by the method described in "(7) Long-term dispersion stability of emulsion" in Examples.
[0141] [Hydrolysis resistance of block copolymer (I) in emulsion]
[0142] If the block copolymer (I) in the emulsion hydrolyzes over time, the number average molecular weight of the block copolymer (I) decreases. The higher the hydrolysis resistance of the block copolymer (I), the more the decrease in the number average molecular weight (Mn) over time can be suppressed.
[0143] The hydrolysis resistance of the block copolymer (I) in the emulsion can be determined by using the retention rate of the number average molecular weight (Mn) obtained by the following formula as an index.
[0144] Number average molecular weight (Mn) retention rate = (number average molecular weight (Mn) of block copolymer (I) after standing at 23°C for 1,000 hours / number average molecular weight (Mn) of block copolymer (I) within 6 hours from emulsion preparation) × 100 (%)
[0145] From the viewpoint of long-term storage stability, the retention rate of the number average molecular weight (Mn) of the block copolymer (I) in the emulsion is preferably 60% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more.
[0146] In addition, in this specification, "number average molecular weight (Mn)" is a value calculated|required by gel permeation chromatography (GPC), and can be specifically measured by the method described in an Example.
[0147] [Viscosity of emulsion]
[0148] From the viewpoint of handling properties, the viscosity of the emulsion is preferably 10 to 1,000 mPa·s, more preferably 100 to 500 mPa·s, and even more preferably 200 to 350 mPa·s.
[0149] In addition, in this specification, "viscosity" means the viscosity measured under the condition of 23 degreeC using the E type viscometer mentioned later.
[0150] [Method for producing block copolymer (I)]
[0151] The block copolymer (I) can be produced by a known production method.
[0152] A known method for producing the block copolymer (I) is, for example, a method of synthesizing a polyester constituting the polyester unit (b) and subjecting the polyester to a polymerization reaction with lactide.
[0153] The polyester can be synthesized by a known method. For example, the polyester can be synthesized by reacting an aliphatic diol (b1) with an aliphatic dicarboxylic acid (b2) using an esterification catalyst (eg, tin octylate, tin chloride, tin oxide).
[0154] When the polyester and lactide are polymerized, a ring-opening polymerization catalyst (eg, tin octylate, tin chloride, tin oxide) is preferably used. The polymerization reaction may be solution polymerization, melt polymerization, interfacial polycondensation, etc., and known polymerization reaction conditions may be used.
[0155] Another known method for producing the block copolymer (I) is, for example, a method in which polylactic acid constituting the polylactic acid unit (a) and a polyester constituting the polyester unit (b) are separately synthesized and the polylactic acid and the polyester are reacted.
[0156] Polylactic acid can be synthesized by a known method. For example, polylactic acid can be synthesized by reacting lactic acid by a direct condensation method or by reacting lactide by a ring-opening polymerization method.
[0157] When the polylactic acid and the polyester are polymerized, an esterification catalyst (eg, tin octylate, tin chloride, tin oxide, etc.) is preferably used. The polymerization reaction may be solution polymerization, melt polymerization, interfacial polycondensation, etc., and known polymerization reaction conditions may be used.
[0158] [Emulsion production method]
[0159] The emulsion can be produced by a known method.
[0160] The emulsion can be obtained by, for example: a pressure dispersion method in which a block copolymer (I), a dispersant (II) and a dispersion medium are simultaneously placed in a closed tank having a stirring device, and the block copolymer (I) is dispersed while being heated and stirred; a direct dispersion method in which a block copolymer (I) is added to a heated dispersion medium containing a dispersant (II) maintained at normal pressure or under pressure and stirred to disperse it; a method in which a block copolymer (I) dissolved in an organic solvent is added to a dispersion medium containing a dispersant (II) and stirred to disperse it; a phase inversion method in which a block copolymer (I) is heated and melted, a dispersion medium is added thereto and stirred to disperse the block copolymer (I) in the dispersion medium, etc., thereby dispersing the block copolymer (I) in the dispersion medium. Even methods other than the above can be appropriately adopted as long as they are methods that can obtain an aqueous dispersion of a biodegradable resin.
[0161] From the viewpoint of enabling simple synthesis, the method for producing the emulsion is preferably a method in which the block copolymer (I) dissolved in an organic solvent is added to a dispersion medium containing a dispersant (II) and stirred to disperse the block copolymer (I), that is, preferably a step of dispersing the block copolymer (I) dissolved in an organic solvent in an aqueous medium in the presence of a dispersant (II).
[0162] When preparing the emulsion, a dispersing device such as a high-pressure homogenizer may be used in combination as necessary.
[0163] Furthermore, from the viewpoint of environmental load, it is preferred that a step of removing the organic solvent is further included after the above-mentioned dispersion step.
[0164] The step of removing the organic solvent is performed by, for example, heating the solution obtained in the above-mentioned dispersing step to remove the organic solvent.
[0165] Furthermore, if necessary, the block copolymer (I), the dispersant (II) and the components other than the dispersion medium may be added to the dispersion medium before dispersing the block copolymer (I), may be added together when dispersing the block copolymer (I), or may be added after dispersing the block copolymer (I).
[0166] Example
[0167] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples.
[0168] The physical properties of the block copolymer (I) and polymers such as polylactic acid in Examples and Comparative Examples were measured or evaluated by the following methods.
[0169] (1) Number average molecular weight (Mn)
[0170] The number average molecular weight (Mn) of the block copolymer (I) and the polymer in the emulsion within 6 hours after the emulsion is prepared is calculated in terms of standard polystyrene (also referred to as the Mn of the polymer) by gel permeation chromatography (GPC). In addition, the Mn of the block structural unit (B) (also referred to as the Mn of the structural unit (B)) is calculated from the Mn of the block copolymer (I) and the mass content of the block structural unit (B).
[0171] 〈GPC measurement conditions〉
[0172] Device: GPC device "HLC-8220" manufactured by Tosoh Corporation
[0173] Separation column: "TSKgel SuperMultiporeHZ-M (column diameter = 4.6 mm, column length = 15 cm)" manufactured by Tosoh Corporation (two columns were connected in series and used)
[0174] Eluent: Tetrahydrofuran (THF)
[0175] Eluent flow rate: 0.35mL / min
[0176] Column temperature: 40°C
[0177] Detection method: Differential refractive index (RI)
[0178] Injection volume: 10 μL
[0179] Concentration: 1 mg / 1 mL ((block copolymer (I) or polylactic acid) / THF)
[0180] (2) (A) / (B) (mass ratio) (mass of the block structural unit (A) mainly composed of the polylactic acid unit (a) / mass of the block structural unit (B) mainly composed of the polyester unit (b))
[0181] pass 1 H-NMR was used to calculate the (A) / (B) (mass ratio) of the block copolymer. The molar ratio of the block structural unit (A) to the block structural unit (B) was calculated from the area ratio of the signal near 5.2 ppm from the polylactic acid unit (a) and the signal near 0.9 ppm from the structural unit (B) containing the polyester unit (b) as the main component in the obtained spectrum. (A) / (B) (mass ratio) was calculated as a mass ratio by multiplying the molar ratio by the molecular weight of the block structural unit.
[0182] 〈 1 H-NMR measurement conditions
[0183] Equipment: Nuclear magnetic resonance equipment "JNM-ECX400" manufactured by JEOL Ltd.
[0184] Solvent: deuterated chloroform
[0185] Measuring temperature: 50℃
[0186] Total times: 1024 times
[0187] (3) Biodegradability (composting)
[0188] The emulsion was cast into a film with a thickness of 100 μm, air-dried for 1 week, dried in a vacuum dryer at 40°C for 8 hours, and then dried at 105°C for 10 minutes, and the biodegradability in compost was measured according to the method based on ISO 14855-2: 2018. The biodegradability in compost was evaluated based on the following evaluation criteria for the decomposition rate after 15 days.
[0189] A: Decomposition rate is 20% by mass or more
[0190] B: Decomposition rate is 10% by mass or more and less than 20% by mass
[0191] C: Decomposition rate is 5% by mass or more and less than 10% by mass
[0192] F: Decomposition rate is less than 5% by mass
[0193] (4) Biodegradability (activated sludge)
[0194] The emulsion was cast into a film with a thickness of 100 μm, air-dried for 1 week, dried in a vacuum dryer at 40°C for 8 hours, and then dried at 105°C for 10 minutes, and the biodegradability in activated sludge was measured according to the method based on ISO 14851: 2019. The biodegradability in activated sludge was evaluated based on the following evaluation criteria for the decomposition rate after 90 days.
[0195] A: Decomposition rate is 30% by mass or more
[0196] B: Decomposition rate is 10% by mass or more and less than 30% by mass
[0197] F: Decomposition rate is less than 10% by mass
[0198] (5) Particle size
[0199] The emulsion was diluted 100 times with ion-exchanged water, and the median diameter (particle size) of particles present in the emulsion was measured by a dynamic light scattering method.
[0200] <Conditions for measuring median particle size>
[0201] Device: Nano-particle analysis device "nano Partica SZ-100" manufactured by Horiba, Ltd.
[0202] (6) Dispersion stability
[0203] After the emulsion was prepared, it was left to stand at 23° C. for 1 day, and the presence or absence of precipitation was visually confirmed. The dispersion stability of the emulsion was evaluated according to the following evaluation criteria.
[0204] A: No precipitation was observed.
[0205] B: Precipitation was confirmed.
[0206] (7) Long-term dispersion stability of emulsion
[0207] After the emulsion was prepared, it was left to stand at 23° C. The presence of precipitation at the bottom of the container was visually checked every week, and the long-term dispersion stability of the emulsion was evaluated according to the following evaluation criteria.
[0208] A: After the emulsion was left to stand for more than 3 months, no precipitation was observed.
[0209] B: After the emulsion was left to stand, precipitation was observed within 1 month to less than 3 months.
[0210] C: After the emulsion was left to stand, precipitation was observed in 2 weeks to less than 1 month.
[0211] F: After the emulsion was left to stand, precipitation was observed in less than 2 weeks.
[0212] (8) Hydrolysis resistance
[0213] After the emulsion was prepared, it was left to stand at 23°C for 1,000 hours, and the number average molecular weight (Mn) of the block copolymer (I) and the polymer (also referred to as Mn of the polymer) was determined by gel permeation chromatography (GPC) in terms of standard polystyrene. Next, the retention rate of the number average molecular weight (Mn), which is an indicator of hydrolysis resistance, was calculated by the following formula.
[0214] Number average molecular weight (Mn) retention rate = (number average molecular weight (Mn) of the block copolymer (I) or polymer after standing at 23°C for 1,000 hours / number average molecular weight (Mn) of the copolymer (I) or polymer determined in (1) above) × 100 (%)
[0215] Based on the calculated retention rate, the hydrolysis resistance of the emulsion was evaluated according to the following evaluation criteria.
[0216] A: The retention rate of number average molecular weight (Mn) is more than 90%
[0217] B: The retention rate of number average molecular weight (Mn) is 80% or more and less than 90%
[0218] C: The retention rate of number average molecular weight (Mn) is 70% or more and less than 80%
[0219] D: The retention rate of number average molecular weight (Mn) is 20% or more and less than 70%
[0220] F: The retention rate of number average molecular weight (Mn) is less than 20%
[0221] It should be noted that the measurement conditions of GPC are the same as those in the above-mentioned “(1) Number average molecular weight (Mn)”.
[0222] (9) Viscosity
[0223] One day after the preparation of the emulsion, the viscosity of the emulsion was measured at 23° C. using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd.). The viscosity of the emulsion was evaluated according to the following evaluation criteria.
[0224] A: 200~350mPa・s
[0225] B: 100~500mPa・s
[0226] C: 10~1,000mPa・s
[0227] D: Separation or precipitation occurred, so it was not a uniform emulsion and could not be measured.
[0228] The block copolymers and polymers in Examples and Comparative Examples were produced by the following methods. The compounds used in Examples and Comparative Examples are as follows.
[0229] 3-Methyl-1,5-pentanediol (manufactured by Kuraray Co., Ltd.)
[0230] Adipic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0231] Succinic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0232] Tin octylate (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0233] Toluene (manufactured by KISHIDA CHEMICAL CO., LTD.)
[0234] L-Lactide (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0235] Methanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0236] 2-Methyl-1,3-propanediol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0237] 2,4-Diethyl-1,5-pentanediol (Tokyo Chemical Industry Co., Ltd.)
[0238] [Example 1]
[0239] In a flask equipped with an apparatus capable of distilling off the generated liquid and a vacuum pump, 3-methyl-1,5-pentanediol and adipic acid were added in a molar ratio of 3-methyl-1,5-pentanediol / adipic acid = 1.1 / 1, and tin octylate was further added in a ratio of 0.1% by mass relative to the total weight of 3-methyl-1,5-pentanediol and adipic acid. The mixture was heated at 160°C for 3 hours under normal pressure and further heated at 220°C for 3 hours under a nitrogen atmosphere, and the reaction was carried out while water was distilled off. Then, the pressure was reduced to 2,000 Pa and the reaction was carried out for 3 hours, and then the pressure was reduced to 80 Pa, and the reaction was carried out while appropriately confirming that the number average molecular weight reached 6,000, thereby synthesizing a polymer composed of a structural unit (B') having a polyester unit as the main component. After the reaction was completed, the pressure was returned to normal pressure, the temperature was cooled to 80°C, and toluene was added to dilute the mixture so that the solid content was 40% by mass, and then the toluene solution was added to methanol in an amount twice the total amount of the solution. The supernatant was discarded, and the same amount of methanol as the amount of the toluene solution was added again for washing. The supernatant was discarded, and the recovered insoluble components were dried at 40° C. using a vacuum dryer to remove organic volatile components, thereby obtaining a polymer composed of structural units (B′) mainly composed of polyester units (b).
[0240] Toluene was added again to the purified polymer composed of structural units (B') to dilute it so that the solid content of the toluene solution of the polymer composed of structural units (B') became 33% by mass, and then the temperature was increased to 140° C. to distill off 10% by mass of the added toluene to dehydrate the system.
[0241] Then, the toluene solution of the polymer composed of the structural unit (B') was cooled to 80°C, and the polymer composed of the structural unit (B') and L-lactide were added so that the polymer composed of the structural unit (B') / L-lactide = 50 / 50, and the weight portion of toluene removed by distillation was further added to adjust the solid content of the toluene solution of the polymer composed of the structural unit (B') and L-lactide to 50% by mass. Then, when the temperature of the above solution was raised to 100°C, 0.1% by mass of tin octylate was added to the polymer composed of the structural unit (B'), and the mixture was reacted for 4 hours, thereby synthesizing a block copolymer (I) composed of a block structural unit (A) mainly composed of a polylactic acid unit (a) and a block structural unit (B) mainly composed of a polyester unit (b), and obtaining a toluene solution of the block copolymer (I).
[0242] Toluene was further added to dilute the solution so that the solid content was 40% by mass, and then the toluene solution having a solid content of 40% by mass was added to methanol in an amount twice the total amount of the solution to precipitate the solid. The methanol in the supernatant was discarded, and methanol in an amount equal to the amount of the toluene solution was added again for washing. The methanol was discarded, and the recovered solid was dried at 40° C. in a vacuum dryer to remove the organic volatile components, thereby obtaining a block copolymer (I) composed of a block structural unit (A) having a polylactic acid unit (a) as the main component and a block structural unit (B) having a polyester unit (b) as the main component.
[0243] The number average molecular weight (Mn) of the obtained block copolymer (I) was 12,000.
[0244] A polymer solution obtained by dissolving the obtained block copolymer (I) in toluene at a concentration of 20% by mass and an aqueous solution obtained by diluting "Kuraray Poval (registered trademark) 22-88" (manufactured by Kuraray Co., Ltd.) as a dispersant with water were mixed so that the dispersant content was 30 phr relative to the block copolymer (I) and the solid content was 10% by mass to obtain 400 g of a mixed solution. The mixed solution was stirred for 5 minutes at a peripheral speed of 17.5 m / s using a precision emulsifying disperser "CLEARMIX" (manufactured by M Technique Co., Ltd.) to obtain a dispersion.
[0245] The dispersion was heated to 85°C, and nitrogen was blown into the gas phase to remove the generated toluene vapor, thereby obtaining an emulsion containing the block copolymer (I) and the dispersant (II). The evaluation results of the biodegradability, particle size, and dispersion stability of the obtained emulsion in activated sludge and compost are shown in Table 1-1.
[0246] [Examples 2 and 3]
[0247] Block copolymers (I) each consisting of a block structural unit (A) consisting of a polylactic acid unit (a) as a main component and a block structural unit (B) consisting of a polyester unit (b) as a main component were synthesized in the same manner as in Example 1, except that the number average molecular weight of the structural unit (B) was adjusted by adjusting the reaction time during the synthesis of the polymer consisting of a structural unit (B') consisting of a polyester unit (b) as a main component, the mass ratio of the polymer consisting of the structural unit (B') to L-lactide used was changed, and the content of the dispersant (II) relative to the block copolymer (I) was changed, thereby obtaining an emulsion.
[0248] The above-mentioned measurements and evaluations were performed on each of the obtained emulsions. The results are shown in Table 1-1.
[0249] [Example 4]
[0250] A block copolymer (I) composed of a block structural unit (A) composed of a polylactic acid unit (a) as a main component and a block structural unit (B) composed of a polyester unit (b) as a main component was synthesized in the same manner as in Example 1, except that 2-methyl-1,3-propanediol was used instead of 3-methyl-1,5-pentanediol, succinic acid was used instead of adipic acid, the reaction time during the synthesis of the polymer composed of the structural unit (B') composed of the polyester unit (b) as a main component was adjusted to adjust the number average molecular weight of the structural unit (B), and the content of the dispersant (II) relative to the block copolymer (I) was changed to obtain an emulsion.
[0251] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-1.
[0252] [Example 5]
[0253] A block copolymer (I) composed of a block structural unit (A) composed of a polylactic acid unit (a) as a main component and a block structural unit (B) composed of a polyester unit (b) as a main component was synthesized in the same manner as in Example 1, except that 2,4-diethyl-1,5-pentanediol was used instead of 3-methyl-1,5-pentanediol, the number average molecular weight of the structural unit (B) was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed of the polyester unit (b) as a main component, and the content of the dispersant (II) relative to the block copolymer (I) was changed, thereby obtaining an emulsion.
[0254] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-1.
[0255] [Example 6]
[0256] The number average molecular weight of the structural unit (B) was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') having the polyester unit (b) as the main component, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle. The same operation as in Example 1 was carried out to synthesize a block copolymer (I) composed of a block structural unit (A) having the polylactic acid unit (a) as the main component and a block structural unit (B) having the polyester unit (b) as the main component, thereby obtaining an emulsion.
[0257] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-2.
[0258] [Example 7]
[0259] A block copolymer (I) composed of a block structural unit (A) having a polylactic acid unit (a) as a main component and a block structural unit (B) having a polyester unit (b) as a main component was synthesized in the same manner as in Example 1, except that “NEOPELEX G-15” (manufactured by Kao Corporation) was used as a dispersant and the content of the dispersant (II) relative to the block copolymer (I) was changed, thereby obtaining an emulsion.
[0260] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-2.
[0261] [Example 8]
[0262] An emulsion was obtained in the same manner as in Example 1 except that the operation of heating the dispersion liquid to remove toluene was not performed.
[0263] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-2.
[0264] [Example 9]
[0265] A block copolymer (I) composed of a block structural unit (A) composed of a polylactic acid unit (a) as a main component and a block structural unit (B) composed of a polyester unit (b) as a main component was synthesized in the same manner as in Example 1, except that succinic acid was used instead of adipic acid, the number average molecular weight of the structural unit (B) was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed of the polyester unit (b) as a main component, and the content of the dispersant (II) relative to the block copolymer (I) was changed, thereby obtaining an emulsion.
[0266] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-2.
[0267] [Example 10]
[0268] A block copolymer (I) composed of a block structural unit (A) composed of a polylactic acid unit (a) as a main component and a block structural unit (B) composed of a polyester unit (b) as a main component was synthesized in the same manner as in Example 1, except that 2-methyl-1,3-propanediol was used instead of 3-methyl-1,5-pentanediol, the number average molecular weight of the structural unit (B) was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed of the polyester unit (b) as a main component, and the content of the dispersant (II) relative to the block copolymer (I) was changed, thereby obtaining an emulsion.
[0269] The obtained emulsion was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1-2.
[0270] [Comparative Example 1]
[0271] 0.1 mass % of tin octylate was added to L-lactide at 200° C. and reacted until the molecular weight reached 40,000, thereby obtaining polylactic acid.
[0272] The obtained polylactic acid was dissolved in dichloromethane at a concentration of 20% by mass to obtain a polymer solution, and an aqueous solution obtained by dissolving "NEOPELEX G-15" (manufactured by Kao Corporation) as a dispersant (II) in water was mixed so that the content of the dispersant (II) was 5 phr relative to the polylactic acid and the solid content was 10% by mass to obtain 400 g of a mixed solution. The mixed solution was stirred for 5 minutes at a peripheral speed of 17.5 m / s using a precision emulsifying disperser "CLEARMIX" (manufactured by M Technique Co., Ltd.) to obtain a dispersion.
[0273] The dispersion was heated to a temperature of 38° C., and nitrogen was appropriately blown into the gas phase to remove the generated methylene chloride vapor, thereby obtaining an emulsion containing polylactic acid and a dispersant.
[0274] The above-mentioned measurements and evaluations were performed on the obtained emulsion. The results are shown in Table 2. The obtained emulsion had poor biodegradability. This is considered to be because the polylactic acid did not have the above-mentioned structural unit (B).
[0275] [Comparative Example 2]
[0276] The production of an emulsion was attempted in the same manner as in Example 1 except that no dispersant was used. However, the block copolymer could not be dispersed to form an emulsion, the particle size could not be measured, and the dispersion stability was also poor.
[0277] [Table 1-1]
[0278]
[0279] [Table 1-2]
[0280]
[0281] [Table 2]
[0282]
[0283] The compounds represented by the abbreviations in Tables 1-1, 1-2 and 2 are as follows.
[0284] PLLA: Poly L-lactic acid
[0285] MPD: 3-Methyl-1,5-pentanediol
[0286] DEPD: 2,4-diethyl-1,5-pentanediol
[0287] MPDiol: 2-methyl-1,3-propanediol
[0288] AA: Adipic acid
[0289] SA: Succinic acid
[0290] As shown in the examples, the emulsion of the present embodiment containing the block copolymer (I) and the dispersant (II) has good biodegradability, wherein the block copolymer (I) includes the block structural unit (A) mainly composed of the polylactic acid unit (a) and the block structural unit (B) mainly composed of the polyester unit (b). Therefore, the industrial usefulness of the emulsion of the present embodiment is extremely high.
Claims
1. An emulsion comprising a block copolymer (I) and a dispersant (II), The block copolymer (I) comprises a block structural unit A and a block structural unit B, wherein the block structural unit A comprises a polylactic acid unit (a) as a main component and the block structural unit B comprises a polyester unit (b) as a main component.
2. The emulsion according to claim 1, wherein The block copolymer (I) accounts for 50% by mass or more and 99% by mass or less relative to 100% by mass of the total of the block copolymer (I) and the dispersant (II).
3. The emulsion according to claim 1 or 2, wherein The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). The aliphatic diol (b1) is a diol having an alkyl group as a branch chain.
4. The emulsion according to claim 3, wherein The aliphatic diol (b1) has 10 or less carbon atoms.
5. The emulsion according to claim 3 or 4, wherein The aliphatic diol (b1) has 5 or more carbon atoms.
6. The emulsion according to any one of claims 3 to 5, wherein The branched chain of the aliphatic diol (b1) is a methyl group.
7. The emulsion according to any one of claims 1 to 6, wherein The block structural unit A accounts for 5 mass % or more and 95 mass % or less relative to 100 mass % of the total of the block structural unit A and the block structural unit B.
8. The emulsion according to any one of claims 1 to 7, wherein The dispersant (II) is a vinyl alcohol polymer. 9 . The emulsion according to claim 1 , wherein the particle size is 100 nm to 1000 nm.
10. A method for producing an emulsion, which is the method for producing an emulsion according to any one of claims 1 to 9, comprising: A step of dispersing the block copolymer (I) dissolved in an organic solvent in an aqueous medium in the presence of the dispersant (II). The method for producing an emulsion according to claim 10 , further comprising a step of removing the organic solvent.
Citation Information
Patent Citations
Aqueous dispersion system of biodegradable resin
JP2004099883A
Biodegradable polyester-based resin fine particle and method for producing the same
JP2005002302A
Aqueous hydrolytically stable dispersions of biodegradable polymers
JP2019507229A